Treatment of a dairy effluent by classical electrocoagulation and indirect electrocoagulation with aluminum electrodes - Tchamango, Serge Raoul; Wandji Ngayo, Kevine; Belibi Belibi, Placide Désiré; Nkouam, Francine; Ngassoum, Martin Benoît (Separation science and technology, 2021)
Classical electrocoagulation and indirect electrocoagulation were applied to an artificial dairy effluent, by imposing a 0.2 A current intensity and varying the treatment time. The influence of the supporting electrolyte and the initial pH on the turbidity, phosphates and organic matter removals was studied. The results showed that optimum removals were reached at pH 7 with calcium chloride as supporting electrolyte. The post-electrocoagulation showed that the treated effluent can be reused during 45 h. The turbidity and phosphates results of electrocoagulation with open circuit were almost identical than that of classical electrocoagulation, but that of organic matter remained weaker.